Analysis of Lobster Seed Export Policy on the National Economy in a Positive Legal System - Priska Khairunnisa; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Indonesia is rich in diversity of marine biota because it is one of the countries that has a wider sea area than its land. Lobster is one of Indonesia's wealth, which is abundantly available and is the most sought-after commodity, even the seeds are exported to foreign countries. The existence of this writing is that the author wants to know how the government regulates the policy of exporting lobster seeds, in fact it is permissible or not since or before the corruption case of the former Ministry of Maritime Affairs and Fisheries and also wants the public to know how influential the export of lobster seeds is for the country's economy. By using descriptive research methods, the authors can compile the article based on existing data and regulations. Policies for lobster seed export activities have different opinions based on their interests. There are contras with the reason that it can harm the country because the selling value is lower than the sale value of lobsters that are already large, it is detrimental to fishermen because if the seeds are exported it results in the availability of large lobsters being small or even threatened to be non-existent, it is profitable for importing countries because the supply of lobsters will be more in imported countries , damage the marine ecosystem, rampant etc. Then, some people who are pro with the lobster seed export policy reasoned that if the export of seeds is prohibited or caught it can harm fishermen who used to export lobster seeds as a livelihood, lobster seeds can be eaten by other predators if left at sea, etc. Besides that, the government with its latest regulation prohibits the export of seeds and allows more if the seeds are bred according to the terms and conditions that have been regulated. Therefore, the government must be wise in making decisions, prioritizing the welfare of the community in the future and the welfare of natural resources.